Assessment of kidney volumes from MRI: acquisition and segmentation techniques - Zöllner, Frank G.; Schad, Lothar R. (American journal of roentgenology, 2012)
Assessment Goals in Kidne...Acquisition Techniques fo...Segmentation Methods for ...Future PerspectivesReferencesCITING ARTICLES OBJECTIVE. The prevalence of chronic kidney disease (CKD) is increasing worldwide. In Europe alone, at least 8% of the population currently has some degree of CKD. CKD is associated with serious comorbidity, reduced life expectancy, and high economic costs; hence, early detection and adequate treatment of kidney disease are important. CONCLUSION. We review state-of-the-art MRI acquisition techniques for CKD, with a special focus on image segmentation methods used for the estimation of kidney volume.